Prevalence and Correlates of Sex Trafficking among Homeless and Runaway Youths Presenting for Shelter Services. (15th February 2019) - Greeson, Johanna K P; Treglia, Daniel; Wolfe, Debra Schilling; Wasch, Sarah
Abstract: The study reported in this article assessed prevalence and demographic correlates of sex trafficking in a purposive sample of 270 young people experiencing homelessness in three U.S. cities (Philadelphia; Phoenix; and Washington, DC) and at five host agencies. Participants were 57% male, 38% female, 4% transgender, and 1% other. The average age of participants was 20.7 years ( SD = 2.0 years). The majority of the participants were African American (56%), followed by white (14%) and multiracial (14%). The Human Trafficking Interview and Assessment Measure detected that nearly one in five young people were victims of sex trafficking, either due to force, fraud, or coercion (FFC); age; or both. Those who were sex trafficked were more likely than those who were not sex trafficked to be female, sexual minorities, or Latino and to have either dropped out of high school or obtained a GED. Differences between being trafficked due to FFC and being trafficked due to age were also investigated. Findings support the need for development of targeted prevention and intervention efforts for young people experiencing homelessness that address sex trafficking victimization and related risk factors.